"It is like an endless guilt trip" - Greco-Roman wrestlers` willingness to train and compete with pain and/or injuries - Tronstad, M.; Aspvik, N. P.; Abrahamsen, F.; Sæther, S. A. (International Journal of Sports Science & Coaching, 2025)
The aim of this study was to examine factors that impact wrestlers` decision-making related to their willingness to train and compete with pain and/or injuries. Five Greco-Roman male wrestlers from Norway, with a mean age of 27.0 (SD = 2.55), were interviewed about their decision-making process when dealing with pain and/or injury. The foundation for the study was based on a decision-based framework for presenteeism and absenteeism in athletes outlined by Mayer and Thiel.(Mayer J, Giel KE, Malcolm D, et al. Compete or rest? Willingness to compete hurt among adolescent elite athletes. Psychol Sport Exerc 2018; 35: 143-150.) The thematic analysis identified three themes: 1) personal self-expectations, 2) the wrestling culture, and 3) post career health. Overall, all the wrestlers expressed a high degree of willingness to risk their bodies physically to achieve top results in competitions. A strong desire to compete, athletic identity, a normalized pain culture, and fear of long-term consequences are the main factors impacting the wrestler's choice to train or compete with pain and/or injury.